Data on the Effects of sterilization on composition and bacterial utilization of dissolved organic carbon - Lindström, Eva S.; Andersson, Martin (Uppsala University, 2018)
Data for the article with the title "Effects of sterilization on dissolved organic carbon (DOC) composition and bacterial utilization of DOC from lakes", further included in Martin Andersson's dissertation "Extent and limitations of functional redundancy among bacterial communities towards dissolved organic matter".

In the study, we conducted a sterilization experiment with DOC from 4 boreal lakes treated with 4 sterilization methods, i.e. 2 filtrations (0.2 µm, 0.1 µm) and 2 autoclaving approaches (single and double autoclaving with a single pH adjustment). Quantity and spectroscopic properties of DOC, before and after sterilization, were studied, and DOC was further tested as a substrate for bacterial growth.

Data includes Bacterial abundance, PARAFAC data, TOC raw data and carbon concentration.

The dataset was originally published in DiVA and moved to SND in 2024.
Data on the Effects of sterilization on composition and bacterial utilization of dissolved organic carbon
Keywords: Biology with specialization in Limnology; Biologi med inriktning mot limnologi; Ecology; Ekologi